Catalyzing Digital Governance: An Innovative E-Government Model to Accelerate Public Service Transformation in Palembang City, Indonesia - Mardianto, Mardianto; Hendarso, Yoyok; Efendi, Sofyan; Rafinzar, Rahmat; Khairunnas, Khairunnas (Journal Public Policy, 2025)
This research was conducted to examine the implementation of e-government in supporting the acceleration of public service transformation at the Department of Population and Civil Registry of Palembang City. The theory used in the study refers to the Diffusion of Innovations theory. The research methodology employed is qualitative and descriptive. Both primary and secondary data were used as sources, with data collection techniques including interviews, documentation, observation, and literature review. The results of the study indicate that public service innovation at Palembang City has been quite good, although it has not been fully implemented using digital platforms according to the criteria based on the concept of e-government. Several innovative programs have improved public services compared to previous manual processes, considering the needs of the community. The implementation of innovation was also preceded by trials and evaluations. The challenges faced include a lack of socialization and a traditional mindset that still relies on offline document processing. Additionally, improvements in facilities and infrastructure are needed to ensure that e-Gov-based service systems can function optimally. The Acceleration Model for Public Service Innovation Transformation produced in this research consists of the dimensions of Innovation Advantage, Resource Infrastructure, and Innovation Impact.